Peran Learning Goal Orientation dan Big Five Personality terhadap Adaptabilitas Karier Siswa SMK - Jati Fatmawiyati; Duta Nurdibyanandaru; Dewi Retno Suminar (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2020)
The purpose of this study is to investigate learning goal orientation (LGO) and Big Five Personality in effect with carrier adaptability. This study used quantitative approach. Simple random sampling technique was used to recruit 93 twelve-grades SMKN